Air exposure and cell differentiation are essential for investigation of SARS-CoV-2 entry genes in human primary airway epithelial cells in vitro - Kasper, Brigitte; Yue, Xiaoyang; Goldmann, Torsten; Gülsen, Askin; Kugler, Christian; Yu, Xinhua; Petersen, Frank (Frontiers in Medicine, 2022)
Background In-vitro models of differentiated primary human airway epithelial cells are a valuable tool to study severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Through the use of these models, it has been shown that the expression of SARS-CoV-2 entry genes in human airway epithelia is influenced by various factors such as age, sex, smoking status, and pathogenic conditions. In this study, we aimed to determine the effects of cell culture conditions and donor demographic and clinical characteristics on the expression of SARS-CoV-2 entry genes including angiotensin converting enzyme 2 (ACE2), transmembrane serine protease 2 (TMPRSS2), cathepsin L (CTSL), and tyrosine protein kinase receptor UFO (AXL) in primary airway epithelial cells. Methods Eleven lung cancer patients with or without chronic obstructive pulmonary disease (COPD) or asthma were recruited. Human bronchial epithelial cells (HBEC) or small airway epithelial cells (SAEC) isolated from submerged or air-liquid interface (ALI) cultures were analyzed by quantitative real-time PCR. We also tested for correlations with clinical data. Results In ALI cultures, the expression of AXL was significantly higher in HBEC than in SAEC. In addition, the expression of ACE2, TMPRSS2, and CTSL was significantly increased in both HBEC and SAEC differentiated under ALI conditions compared with the submerged culture. Negligible association was found between the expression of SARS-CoV-2 entry genes in SAEC and the age, sex, smoking status, and complication of COPD, asthma or hypertension of the cell donors. Conclusion These results demonstrate that the expression of SARS-CoV-2 entry genes in differentiated primary airway epithelial cells in-vitro is much more influenced by individual culture conditions than by specific characteristics of individual donors.